PENGARUH PEMBENTUKAN KELOMPOK (TEAM BUILDING) TERHADAP ETOS KERJA DAN KONTRIBUSINYA BAGI PRODUKTIVITAS KERJA INSANI - Asip F. Hadipranata; - Sudardjo (Jurnal Psikologi, 1999)
The purpose of this research is to measure the impact of teambuilding on work ethos and its contribution to human productivity. Many approaches have indicated that cohesive group or teamwork has a positive impact on human productivity. The hypothesis of this research was that teambuilding creates good teamwork or work ethos and give contribution to human productivity. Three hundred and sixty subjects were involved in this study. Subjects were divided into two groups. As the experimental groups, 180 people were divided into 30 small groups, each small group consisted of six people. The remaining became control groups for 180 people. They were also divided into 30 small groups. The result of this study shows that teambuilding has a positive effect on work ethos (t1= 4,789 p < 0,01; t2 = 9,272 p < 0,01) and a high contribution to human productivity (87.5 percent). In conclusion, teambuilding has a positive and steady effect on work ethos and a high contribution to human productivity. Keywords: teambuilding, work ethos, human productivity